Translational efficiency of polycistronic mRNAs and their utilization to express heterologous genes in mammalian cells. - Kaufman, R J (1987)
The translation of polycistronic mRNAs in mammalian cells was studied. Transcription units, constructed to contain one, two or three open reading frames (ORFs), were introduced stably into Chinese hamster ovary cells and transiently into COS monkey cells. The analysis of mRNA levels and protein synthesis in these cells demonstrated that the mRNAs transcribed were translated to generate multiple proteins. The efficiency of translation was reduced approximately 40- to 300-fold by the insertion of an upstream ORF. The results support a modified 'scanning' model for translation initiation which allows for translation initiation at internal AUG codons. High-level expression of human granulocyte-macrophage colony stimulating factor was achieved utilizing a vector that contains a polycistronic transcription unit encoding an amplifiable dihydrofolate reductase marker gene in its 3' end. Thus, polycistronic expression vectors can be exploited to obtain high-level expression of foreign genes in mammalian cells.